The ultimate bicycle owner's manual : the universal guide to bikes, riding, and everything for beginner and seasoned cyclists - Weiss, Eben (Black Dog & Leventhal, 2016)
"Everything you need to know to purchase, maintain, and ride a bike for recreation, commuting, competition, travel, and beyond! From the bike world's most beloved and trusted advocate. Eben Weiss, aka Bike Snob, is the voice of cyclists everywhere. Through his popular blog he has been informing, entertaining, and critiquing the bike-riding community since 2007. With his latest book, The Ultimate Bicycle Owner's Manual, Weiss makes his vast experience and practical advice available to bike "newbies" and veterans alike. Chapters cover Obtaining a Bike, Understanding Your Bike, Maintaining Your Bike, Operating Your Bike, Off-Road Riding, Coexisting with Drivers, Competitive Cycling, Bike Travel, Cycling with Kids, and What the Future Holds for Bikes in our Communities. Weiss's humorous, down-to-earth style takes all the mystery and intimidation out of cycling and will inspire even the most hesitant couch potato to get out and ride! Eben Weiss is the blogger behind bikesnobnyc.blogspot.com and the author of Bike Snob, Bike Snob Abroad, and The Enlightened Cyclist. He also writes for Bicycling magazine and lives in New York." --